Zagreb as Croatia's core region - Drazen Njegac; Ivo Nejasmic (European Regional Science Association (ERSA), 2002)
At the country-wide level, core regions can clearly be discerned from peripheral regions in Croatia. The Zagreb region accounts for only 8.7% of Croatia's surface area, yet its importance distinguishes it as a exceptional core region. A total of 27.8% of Croatia's population lives in it (2001), while 29.9% of its working population is employed there (1991). In the city of Zagreb itself, the equivalent shares are approximately one sixth (17.6% of the population, 18.2% of all employed). Within the region itself, this concentration and centralization are even more marked, particularly in terms of labor. Zagreb accounts for approximately three fifths of the population and over three quarters of the employed of the wider Zagreb region, while the urban agglomeration, formed as a result of intensified suburbanization, encompasses approximately 80% of the population and almost 90% of the employed. Realistically, therefore, only the Zagreb urban region, i. e. the Zagreb agglomeration, can be referred to as a core region. Zagreb's importance came to the forefront after Croatia attained independence in 1991. Zagreb then became the political center of the new state, which further enhanced its functions and deepened the differences between it and other cities. A large concentration of the country's population, a high degree of urbanization and dynamic economic development, particularly in the tertiary sector, contributed to these processes considerably. A comparison of population trends in Zagreb and Croatia's remaining three macro-regional hubs, Split, Rijeka and Osijek, additionally confirms the aforementioned processes. During the 1991-2001 period, the differences between Zagreb and these three remaining centers grew. Thus the ratio between Zagreb and the country's second largest city, Split, increased from 1:3.7 (1991) to 1:3.9 (2001), while the ratio betwwen Zagreb and Rijeka went from 1:4.2 to 1:4.8, and between Zagreb and Osijek from 1:6.7 to 1:7.5. This ocurred under conditions marked by the considerable decline of Croatia's population, which had less of an impact on the core region, while almost all other regions and large cities in Croatia were affected by depopulation. This means that the order of size of Croatian cities is even more irregular now than it was ten years ago and this in turn indicates increasing monocentrism. A further indicator is the number and share of business entities in Croatia: 75% of the largest Croatian corporations (15 out of 20), 45% of Croatia's banks (21 out of 47) and 67% of the largest Croatian retail/wholesale companies (12 out of 18) are headquartered in Zagreb. The most important transit routes are also centered in Zagreb, regardless of whether it is a matter of road, rail, air or telecommunications routes. However, the links between Zagreb and the remaining macro-regional centers, particularly Split, are unsatisfactory. In this manner, the remaining settlements are additionally left behind in integration with European developmental trends. Generally the overall economic development of other parts of Croatia considerably lags behind that of the central, Zagreb area, which is reflected in unequal regional development.
Keywords: 330